Saving and Investment Nexus in Indonesia: Revisiting Feldstein-Horioka Hypothesis - Febriani, Ratu Eva; Ekaputri, Retno Agustina; Armelly, Armelly - (Universitas Bangka Belitung, 2024)
The Indonesian economy cannot be separated from interaction with the economies of other countries, so changes in global conditions will also affect the Indonesian economy. A significant investment is needed to drive the domestic economy, while domestic capital accumulation is still insufficient. The relationship between savings and investment put forward by Feldstein and Horioka (FH) was reviewed for the case of Indonesia from 1981 to 2020. The VECM found a long-term and short-term relationship and a bidirectional Granger causality between saving and investment. The strength of the saving-investment correlation confirms the validity of the FH hypothesis in Indonesia.